INFLUENCE OF VACUUM INSTILLATIONS WITH INTRAVENOUS INTRODUCTION OF NITROGEN OXIDE DONATORS ON THE HEALING OF PURULENT SOFT TISSUE WOUNDS - Horodova-Andrieieva, T.V.; Liakhovskyi, V.I.; Sydorenko, A.V. (World of Medicine and Biology, 2022)
The efficacy of vacuum therapy with instillations of L-arginine was studied in combination with its intravenous infusion. Results were in 89 patients, treated for purulent-necrotic soft tissue diseases. Patients were emergency operated on. The main group 44 patients, got the same therapy and intravenous 100 ml of arginine hydrochloride solution daily. 2 3 courses of vacuum therapy, 3 days each were performed. In the main group, signs of intoxication and body temperature returned to normal by an average of 3.1 days. Normalization of the level of leukocytes was observed in 5.4 days. pH-metry from the wound surface, it was found that significant changes in the average pH of patients in the main group were observed for 7 10 days - the beginning of the regeneration phase. The therapy in the main group in comparison with typical local treatment provided accelerated wound cleansing, reduction of microbial contamination and faster transition of purulent-necrotic phase to regeneration.
Keywords: purulent-necrotic diseases; vacuum therapy; instillations; arginine; wound healing